An improvement of competitive exercises performing on the rings by 10-12 year old gymnasts using special physical training - Deyneko, A. (Slobozhanskyi herald of science and sport, 2017)
Purpose: to reveal the influence of the level of special physical readiness of gymnasts of 10-12 years on the technique of performing exercises on rings.